Synergistic effects of dietary oxolinic acid combined with oxytetracycline on nonspecific immune responses and resistance against Vibrio parahaemolyticus infection of white shrimp (Penaeus vannamei). Issue 127 (August 2022) - Huang, Huai-Ting; Chang, Jui-Jen; Lin, Yu-Ru; Chen, Yin-Yu; Wu Chang, Yung-Han; Chen, Bo-Ying; Nan, Fan-Hua
Abstract: This study investigated the synergistic effects of oxolinic acid (OA) combined with oxytetracycline (OTC) on white shrimp ( Penaeus vannamei ). Disk diffusion susceptibility testing was performed to analyze the sensitivity of Vibrio alginolyticus and Vibrio parahaemolyticus to different concentrations of OA and OTC. The results revealed that 50 mg OA/L combined with 50 mg OTC/L exhibited stronger antibacterial effects on V. alginolyticus and V. parahaemolyticus . The results of in vitro tests indicated that cotreatment with OA and OTC significantly reduced superoxide anion production and phenoloxidase activity, but not phagocytic activity. Subsequently, feeding trials were performed to investigate the immunomodulatory effects and bioaccumulation of dietary OA combined with OTC on shrimp. The healthy shrimp (15.13 ± 1.02 g) were divided into four groups: control, 100 mg OA/kg combined with 50 mg OTC/kg, 50 mg OA/kg combined with 100 mg OTC/kg, and 50 mg OA/kg combined with 50 mg OTC/kg. The shrimp were sampled to determine innate immunity parameters and residual OA and OTC levels in the muscle during a 28-day feeding regimen; the shrimp were fed the experimental diet from day 1 to day 5 and a commercial diet from day 6 to day 28. Residual OA levels were considerably higher in the group fed 100 mg OA/kg combined with 50 mg OTC/kg compared with the other groups and peaked on day 4. The residual OA levels of all the groups were below the detection limit after without providing OA. The residual OTC levels of the group fed 50 mg OA/kg combined with 100 mg OTC/kg were considerably higher from day 1 to day 4. The residual OTC levels in all the groups decreased rapidly and could not be detected on day 28. The administration of 50 mg OA/kg combined with 100 mg OTC/kg exerted the least effect on the white shrimp. Moreover, the survival rates of the treatment groups after the V. parahaemolyticus challenge were higher than those of the control group, especially the group fed 50 mg OA/kg combined with 100 mg OTC/kg. This result indicated that the synergistic effects of dietary OA and OTC are safe and effective. Combination therapy is a new method of antibiotic use in aquaculture. Highlights: 50 mg OA/kg plus 50 mg OTC/kg exhibited stronger antibacterial effects on Vibrio alginolyticus and Vibrio parahaemolyticus. The administration of 50 mg OA/kg combined with 100 mg OTC/kg exerted the least effect on the white shrimp. Shrimp fed with 50 mg OA/kg plus 100 mg OTC/kg could against Vibrio parahaemolyticus infection and no drug residue concerns.